Baseflow analysis using master recession curves and numerical algorithms in mountain basins: Suratá's river and Oro's river (Santander, Colombia) (2016)
The interaction between groundwater inflow and outflow is complex in streams connected from aquifers located in fractured rock media. The recession curves of hydrographs provide information about these hydrogeological processes and they are useful to assess an insight in the storage-discharge relationship in subsurface reservoirs. In this study, the physic base and the nonlinearity relationship of storagedischarge were analyzed through a mathematical expression which describe a master recession curve. Four numerical algorithms were applied to estimate the baseflow of the Suratá's River basin and the high Oro's River basin, Santander-Colombia. In both cases, master recession curves showed the nonlinearity relationship in storage-discharge. Furthermore, the exponent values and the proportionality constants give additional information about the aquifers in contact to the river and the special scale of recharges that may occur in these aquifers.